Remodelling the Growth Inhibition Kinetics of Pseudomonas sp. Strain DrY Kertih on Acrylamide (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
The bacterium Pseudomonas sp. strain Dr Y Kertih is an efficient acrylamide-degrader isolated from hydrocarbon sludge and is able to tolerate high concentrations of acrylamide. Modelling was carried out using several other kinetic models such as Haldane, Andrews Noack, the Web and Yano, Luong, Teissier and Hans-Levenspiel. The statistical analysis and accuracy of the all seven kinetic models used indicated that Aiba was the best model with small values for RMSE and AICc, closest to unity for adjusted R2 values, and Bias Factor and Accuracy Factor nearest to unity. The Aibaâ€™s constants; maximal growth rate, half-saturation constant for maximal growth and inhibition constant represented by ïmax, Ks and Ki, were 0.221 per h (95% C.I., 0.140 to 0.301), 128.9 mg/L (95% C.I., 40.4 to 217.4) and 633.8 mg/L (95% C.I., 458.6 to 808.9), respectively. The true maximal reduction rate, which occurred when the slope of the curve is zero occurs at 229 mg/L acrylamide concentration and a corresponding value of 0.099 hr-1 (95% C.I., 0.063 to 0.135). The modelling of toxicant bacterial growth kinetics is an integral part of improving effective bioremediation strategies as the consistencies obtained can be used to plan and strategize bioremediation constraints. To date, based on the specific maximal growth rate on acrylamide for this bacterium, it indicates it is the most efficient acrylamide-degrading strain
Keywords: biodegradation acrylamide; Antarctica; substrate inhibition; Aiba model